Influences of ambient gases upon emission characteristics of Mo-FEAs during frit sealing process - Kim, Hoon; Ju, Byeong Kwon; Lee, Kwang Bae; Kang, Moon Sik; Jang, Jin; Oh, Myung Hwan (Proceedings of the IEEE International Vacuum Microelectronics Conference, IVMC, 1998)
The influences of ambient gases on the packaging of Spindt-type Mo-field emitter arrays (FEAs) at the atmosphere were studied through electrical field emission characteristics and Mo surface analysis according to various ambient gases (N2, AR and air). And electrical field emission characteristics in ultra high vacuum chamber and Mo surface analysis were performed after breaking the sealing lines to expose the FEAs. We can obtain increased electron emission current for each pixel by using Ar gas when compared with other gases during frit process.